Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Discovery Learning di Kelas V Sekolah Dasar Negeri 65 Pekanbaru - Azzahra, Farisa Miftahul; Zainil, Melva (Universitas Negeri Padang, 2024)
The purpose of writing is to describe the increase in student learning outcomes when implementing integrated thematic learning with the Discovery Learning model. This type of research is classroom action research using qualitative and quantitative approaches. The research process consists of planning, implementing, observing and reflecting. The subjects of this study were fifth grade students at SDN 65 Pekanbaru. The results showed an increase in: a) lesson plans in cycle I obtained an average of 88.64% (B), increased in cycle II obtained a percentage of 93.7% with (SB), b) teacher activity in cycle I obtained an average average 81.25% (C), increased in cycle II to obtain a percentage of 93.75% (SB), c) student activity in cycle I obtained an average of 81.25% (C), increased in cycle II to obtain a percentage of 93, 75% (SB), and d) student learning outcomes in cycle I obtained an average value of 73.94 (C), increased in cycle II obtained an average value of 84.22 (B). From the results of the research conducted, it can be concluded that integrated thematic learning using the Discovery Learning model can improve the learning outcomes of fifth grade students at SDN 65 Pekanbaru.